Familiengründung mittels Eizellspende Zur Ethik einer reproduktionsmedizinischen Praxis in der liberalen Gesellschaft - Heyder, Clemens (Studien zu Wissenschaft und Ethik, 2023)
A strict ban on egg donation is unjustified in a liberal society. Yet, egg donation is nevertheless fraught with problems that should not be ignored. This work examines those problems from a moral philosophical perspective and identifies frameworks for dealing with egg donation appropriately. In addition, numerous interfaces with other reproductive procedures are highlighted.